2021
DOI: 10.3390/ijerph182413269
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Impact of COVID-19 on Pathology Laboratories and Cancer Diagnosis in Girona

Abstract: Introduction: The recent COVID-19 pandemic has compromised socio-health care, with consequences for the diagnosis and follow-up of other pathologies. The aim of this study was to evaluate the impact of COVID-19 on cancer diagnosis in Girona, Spain. Methodology: Observational study of samples received in two pathology laboratories during 2019–2020 (tertiary hospital in Girona and county hospital in Figueres). Date, sample type, and location and morphology were available. Samples were recoded to determine malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In the first pandemic wave, health systems were subjected to sudden and overwhelming pressure. 2 , 3 In cancer, this meant delaying diagnoses 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 and altering treatment regimens. 30 , 31 , 42 , 43 , 44 , 45 , 46 , 47 Subsequent pandemic waves, including the one linked to the omicron variant, have triggered new health crises.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first pandemic wave, health systems were subjected to sudden and overwhelming pressure. 2 , 3 In cancer, this meant delaying diagnoses 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 and altering treatment regimens. 30 , 31 , 42 , 43 , 44 , 45 , 46 , 47 Subsequent pandemic waves, including the one linked to the omicron variant, have triggered new health crises.…”
Section: Introductionmentioning
confidence: 99%
“… 38 Meanwhile, a study based on two hospital pathology laboratories reported a decrease of 6% to 20% until December 2020. 40 …”
Section: Introductionmentioning
confidence: 99%
“…The total number of pathology reports was reduced by Several studies examine the post-pandemic period from various perspectives and report similar findings. Admissions to dermatology outpatient departments [47][48][49][50], samples submitted to pathology [51] and cytology [52,53] laboratories, and elective surgical procedures performed [54,55] all decreased; however, the distribution of cases varied depending on the region where the study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact on the cancer stage is unknown. However, no differences have been observed in the prevalence of cancer diagnoses in pathology records from 2019 and 2020 in two hospitals in Girona ( 16 ).…”
Section: Introductionmentioning
confidence: 94%